2020
DOI: 10.1002/mats.202000055
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Simulation and Warping Deformation Experimental Study of PEEK in Material Extrusion

Abstract: Ceramic materials, including alumina and zirconium oxide are mainly formed by 3D printing (3DP) and sintering. [8,9] However, this technique results in up to 40% volume shrinkage in the model and finding an appropriate binder is an enormous challenge. [10] Recently, polyether-ether-ketone (PEEK) has been proposed as a dental implant material. Studies have shown that PEEK is a semicrystalline thermoplastic with a melting point of 343 °C and a glass transition temperature of 143 °C. It has beige appearance, reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This is because, as nozzle temperature increases, the residual stress decreases, resulting in a decrease in warpage. However, a higher nozzle temperature could lead a higher temperature difference between extruded filament and printing chamber, which will result in a larger thermal gradient in the samples [ 54 ]. Therefore, it can be seen that, as the temperature increases, the tendency of warpage to decrease gradually slows down.…”
Section: Resultsmentioning
confidence: 99%
“…This is because, as nozzle temperature increases, the residual stress decreases, resulting in a decrease in warpage. However, a higher nozzle temperature could lead a higher temperature difference between extruded filament and printing chamber, which will result in a larger thermal gradient in the samples [ 54 ]. Therefore, it can be seen that, as the temperature increases, the tendency of warpage to decrease gradually slows down.…”
Section: Resultsmentioning
confidence: 99%
“…Stress-relieving techniques were suggested in literature to enhance the quality of the final product. Han et al [29] numerically studied the effect of different processing parameters on the temperature and stress distributions of PEEK during the extrusion process. They found that uneven temperature and stress distributions in the material enhanced warping deformation.…”
Section: Introductionmentioning
confidence: 99%